BREAKING THE SILENCE OF HIV/AIDS AND SEXUALITY - Mitchell, Yolanda (PINS-Psychology in Society, 2025)
Reddy, V, Sandfort, T and Rispel, A (eds) (2009) From social silence to social science: Same-sex sexuality, HIV & AIDS and gender in South Africa. Cape Town: HSRC Press. ISBN 978-0-7969-2276-2 pbk. Pages xxxiii + 252 . This book is the proceedings of the conference Gender, same-sex sexuality and HIV/AIDS in South Africa: An international conference of researchers, community leaders and activists, held in Pretoria from 9 to 11 May 2007. The aim of conference was to bring together researchers, social scientists, community leaders, activists, programme designers and analysts to review and evaluate the history of research on same-sex sexuality in South-Africa and its possible impact on the HIV/AIDS epidemic, with the purpose of identifying and prioritising future efforts. The proceedings then is a multi-disciplinary collection of articles with which the editors “hope to direct debate and discussion to developing research-based interventions that assist in changing sexual practices that will reduce and ultimately end HIV infection” (p xxii).